MHC I-dependent antigen presentation is inhibited by poliovirus protein 3A - Deitz, Stephen B. (The National Academy of Sciences, 2000)
The effects of poliovirus 3A protein expression and poliovirus infection on the presentation of hepatitis C virus antigens in cultured chimpanzee cells were examined. Expression of poliovirus 3A protein inhibits protein secretion when expressed in isolation and was sufficient to protect chimpanzee cells from lysis by hepatitis C virus-specific cytotoxic T cells in standard (51)Cr-release assays. Poliovirus infection also inhibited antigen presentation, as determined by decreased cytotoxic T cell activation. A mutation in 3A that abrogates the inhibition of protein secretion also abolished the effects of poliovirus on antigen presentation. These results demonstrate that the inhibition of secretion observed in poliovirus-infected cells substantially reduces the presentation of new antigens on the cell surface. These observations may reflect a general mechanism by which nonenveloped viruses such as poliovirus and other viruses that do not require a functional protein secretory apparatus can evade detection by the cellular immune response.